2002
DOI: 10.1046/j.1471-4159.2002.01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Erucylphosphocholine‐induced apoptosis in glioma cells: involvement of death receptor signalling and caspase activation

Abstract: Erucylphosphocholine (ErPC) is a promising anti-neoplastic drug for the treatment of malignant brain tumours. It exerts strong anti-cancer activity in vivo and in vitro and induces apoptosis even in chemoresistant glioma cell lines. The purpose of this study was to expand on our previous observations on the potential mechanisms of ErPC-mediated apoptosis with a focus on death receptor activation and the caspase network. A172 and T98G glioma cells were treated with ErPC for up to 48 h. ErPC effects on the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 53 publications
(101 reference statements)
4
19
0
1
Order By: Relevance
“…This inhibitory effect is very similar to that of ET-18-OCH 3 and other alkylphosphocholines (Boggs et al, 1995a,b;Ramos et al, 2002) used as anticancer drugs. It has been reported recently that the antitumoral drug erucylphosphocholine exerts an apoptotic effect on glioma cells, including the processing of procaspases-3, -7, -8, and -9 into the active forms; interestingly, caspase inhibitors prevented apoptosis but did not abrogate cell death (Kugler et al, 2002), providing evidence for the existence of a caspase-independent pathway turned on by this drug. In the search for the molecular basis of the cytotoxicity of erucylphosphocholine, these authors demonstrate the lack of involvement of the TNF or TNFrelated ligand apoptotic pathways.…”
Section: Discussionmentioning
confidence: 97%
“…This inhibitory effect is very similar to that of ET-18-OCH 3 and other alkylphosphocholines (Boggs et al, 1995a,b;Ramos et al, 2002) used as anticancer drugs. It has been reported recently that the antitumoral drug erucylphosphocholine exerts an apoptotic effect on glioma cells, including the processing of procaspases-3, -7, -8, and -9 into the active forms; interestingly, caspase inhibitors prevented apoptosis but did not abrogate cell death (Kugler et al, 2002), providing evidence for the existence of a caspase-independent pathway turned on by this drug. In the search for the molecular basis of the cytotoxicity of erucylphosphocholine, these authors demonstrate the lack of involvement of the TNF or TNFrelated ligand apoptotic pathways.…”
Section: Discussionmentioning
confidence: 97%
“…The tumor cells propagate rapidly in brain tissue, often rendering difficulty in antitumor treatments as well as complete surgical resection. 23 It was shown that the resistance to anticancer treatment was partially due to a dysfunction of an apoptotic program in the tumors. 24 In our work, PEDF expression elicited a significant increase of apoptosis to the treatment with 100 mM H 2 O 2 , although no significant change in apoptosis was observed with low doses of H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative Analysis of Apoptosis-Cytoplasmic histone-associated DNA fragments indicative of ongoing apoptosis were measured using the cell death kit following the manufacturer's instructions as described previously (8). Briefly, for apoptosis induction, 1 ϫ 10 4 human glioma or Jurkat cells were seeded in 96-well microtiter plates and treated after 24 h with various drugs or with vehicle as control for 12 h. To analyze the effects of the inhibitors on ErPC3-induced apoptosis, the cells were preincubated for 1 h with CsA or oligomycin before treatment with ErPC3 at 45 M (U87MG), 15 M (U118MG), or 25 M (Jurkat).…”
Section: Methodsmentioning
confidence: 99%
“…The precise mechanisms of antineoplastic activity of alkylphosphocholines are unknown. It has been found that they are working through p53-independent pathways (2,8) involving mitochondrial alteration, cytochrome c release, and caspase-3 activation (9). Our previous studies have shown that the pro-apoptotic activity of ErPC3 is associated with an increased production of reactive oxygen species (10) and might be blocked by ligands of the peripheral-type benzodiazepine receptor (11), which is located in the outer membrane of mitochondria in close proximity to the voltage-dependent anion channel (12).…”
mentioning
confidence: 99%